Refining Metabolic Mass Transfer for Efficient Biosynthesis of Plant Natural Products in Yeast - Xue, Haijie; Sun, Wentao; Wang, Ying; Li, Chun (Frontiers in Bioengineering and Biotechnology, 2021)
Plant natural products are important secondary metabolites with several special properties and pharmacological activities, which are widely used in pharmaceutical, food, perfume, cosmetic and other fields. However, the obtain of these compounds mainly relies on phytoextraction from natural plants. Due to the low contents in plants, phytoextraction has disadvantages of low production efficiency and severe environmental and ecological problems, restricting its wide applications. Therefore, microbial cell factory especially yeast cell factory has become an alternative technology platform for heterologous synthesis of plant natural products. Many approaches and strategies have been developed to construct and engineer the yeast cells for efficient production of plant natural products. Meanwhile, metabolic mass transferring has been proven to be important to improve the heterologous production. Transmembrane mass transferring and intracellular mass transferring are two major forms of metabolic mass transferring in yeast, which can be modified and optimized to improve the production efficiency, reducing the consumption of intermediate and eliminating the feedback inhibition. This review summarized different strategies (in figure 1) of refining metabolic mass transferring process to enhance the production efficiency of yeast cell factory, providing approaches for further studying on the synthesis of plant natural products in microbial cell factory.